How Does Trade Evolve in the Aftermath of Financial Crises? - Abiad, Abdul; Mishra, Prachi; Topalova, Petia (Washington, D.C. : International Monetary Fund, 2011)
We analyze trade dynamics following past episodes of financial crises. Using an augmented gravity model and 179 crisis episodes from 1970-2009, we find that there is a sharp decline in a country's imports in the year following a crisis-19 percent, on average-and this decline is persistent, with imports recovering to their gravity-predicted levels only after 10 years. In contrast, exports of the crisis country are not adversely affected, and they remain close to the predicted level in both the short and medium-term.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet